Fifty years of the cleft centre in Bratislava - Fedeleš, Jozef; Janovič, Jozef; Oravkinová, Zuzana; Klímová, Irena; Fekiačová, Dagmar (Acta chirurgiae plasticae (English ed.), 2004)
In our paper, we would like to present and analyse the activities in the cleft centre in Bratislava between 1952 and 2001. We document the gradual development of the complex treatment and the important changes in the usage of the operative techniques and in the primary and secondary operations timing, as well as the application of the new trends in the field of plastic surgery, maxillofacial surgery, anaesthesiology, orthodontics, speech therapy, paediatrics, human genetics and psychology.
Keywords: nemocniční oddělení; Surgery, Plastic; lidé; rozštěp patra; Hospital Departments; plastická chirurgie; Cleft Palate; Humans; rozštěp rtu; Cleft Lip